Synthesis of ZnO Nanoparticles Doped Zirconium Oxychloride by PSTA BATAN Yogyakarta Production as Photoanode Semiconduktors for Dye Sensitized Solar Cell - Slamet, Domo; Krisdiyanto, Didik; Khamidinal, Khamidinal (Proceeding International Conference on Science and Engineering, 2017)
Dye Sensitized Solar Cell (DSSC) is a device for light conversion to be electrical energy based on the concept of semiconducting sensitivity of the wide gap. This study aims to synthesis nanoparticles of ZnO: Zr semiconductors and tested the performance of ZnO: Zr nanoparticles on the DSSC system. ZnO Doped Zr Nanoparticles from precursor by Science and Technology Acceleration Center of National Nuclear Energy Agency (PSTA BATAN) Yogyakarta production was synthesized by gel-combustion method, and tested its performance on DSSC system. Effect of doping concentration variation Zr (0, 1, 3 and 5%) on the structure crystals and optical properties of ZnO studied by X-ray diffraction, infra-red spectra, and UV-Visible absorbance spectra. In this study also studied about the effect of Zr doping on changes in the parameters of crystal structures such as distances between fields of crystals , crystals lattice (a and c), unit cell volume, crystallite size, microstrain (?), dislocation density (?), and the textural coefficient . The synthesized nanoparticles meet the criteria 3-dimensional nanostructure of hexagonal wurtzite crystals. Uptake ZnO infrared radiation shows an increase in intensity as well shift in wave number 610 - 400 due to doping Zr. Doping Zr also influences the electronic structure of semiconductors characterized by the change of bandgap energy from 3,10-3,05 eV. Semiconductor performance test nanoparticles on the DSSC system showed a 1% Zr doping concentration increasing the voltage by 174 mV and the stability of the solar cell than the cell ZnO solar without doping that produces a voltage of 128 mV.